2003
DOI: 10.1103/physrevb.67.134520
|View full text |Cite
|
Sign up to set email alerts
|

Renormalization of the elementary excitations in hole- and electron-doped cuprates due to spin fluctuations

Abstract: Extending our previous studies we present results for the doping-, momentum-, frequency-, and temperature-dependence of the kink-like change of the quasiparticle velocity resulting from the coupling to spin fluctuations. In the nodal direction a kink is found in both the normal and superconducting state while in the antinodal direction a kink occurs only below Tc due to the opening of the superconducting gap. A pronounced kink is obtained only for hole-doped, but not for electrondoped cuprates and is character… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 41 publications
0
33
0
1
Order By: Relevance
“…29 Counterarguments, disfavouring phonons and attributing the latter phenomena to antiferromagnetic spin fluctuations have been put forward 30 [43,44,42] (see also the discussions in [6,7] which concern experiments as well as those in [5], examining experimental observations in the light of a number of different theoretical possibilities). We do not consider electron-phonon interaction as being the primary cause for the 'kink' in the experimentally measured energy dispersions.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Counterarguments, disfavouring phonons and attributing the latter phenomena to antiferromagnetic spin fluctuations have been put forward 30 [43,44,42] (see also the discussions in [6,7] which concern experiments as well as those in [5], examining experimental observations in the light of a number of different theoretical possibilities). We do not consider electron-phonon interaction as being the primary cause for the 'kink' in the experimentally measured energy dispersions.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…30 For completeness we mention that we fail to comprehend the methodology with the aid of which the authors of [42] deduced from their computational results concerning the singleparticle spectral function (denoted in [42] by N (k, ω)) a kink in the single-particle energy dispersion. In our judgement, connecting the maxima of a series of N (k, ω) corresponding to various k (considered as parameter), as the authors of [42] did (see , noting that in these ω is measured in milielectron volts and k in units of the inverse lattice constant), cannot provide unequivocal information with regard to the dispersion of the underlying single-particle excitation energies. 31 See, for example, Fig.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…In a two-dimensional Hubbard model, it has been reported that the superconducting state has d x 2 Ϫy 2 symmetry by a self-consistent calculation for the full momentum-and frequency-dependent gap [5][6][7][8]. Recently, triplet pairing due to spin-fluctuation exchange of superconductivity in Sr 2 RuO 4 has been discussed in relation to the band structure and spin susceptibility by using a two-dimensional Hubbard model for three bands crossing the Fermi level [9].…”
mentioning
confidence: 99%
“…The coupling terms are semiempirically determined so as to reproduce the experiments as shown in Eqs. (30)- (34). To this end, the interplane coupling (t inter ) is also expressed by the interplane J value in our magnetic (J) model.…”
Section: Ginzburg-landau Model For Multiband Effects For Cuprates Andmentioning
confidence: 99%